Features of new cyclotron resonances, as well as conditions for resonant acceleration of charged particles in a vacuum without a magnetic field - Buts, V.A.; Zagorodny, A.G. (Problems of Atomic Science and Technology, 2023)
It is shown that the known conditions for cyclotron resonances are strictly valid only under autoresonance conditions or in the nonrelativistic case. In other cases, it is necessary to use the conditions established in the present work. The main features of charged particle dynamics under new resonant conditions are presented. Conditions are found for infinite acceleration of electrons by a transverse electromagnetic wave in a vacuum without a magnetic field. Показано, що відомі умови для циклотронних резонансів строго справедливі лише в умовах авторезонансу або в нерелятивістському випадку. В інших випадках необхідно використовувати умови, виписані в роботі. Наведено результати дослідження основних особливостей динаміки заряджених частинок за нових резонансних умов. Знайдено умови необмеженого прискорення електронів поперечною електромагнітною хвилею у вакуумі без магнітного поля.